Growth and Development in Preterm Infants: What is The Long-Term Risk? - Bernie Endyarni Medise (Amerta Nutrition, 2021)
ABSTRACT Background: Indonesia comes in the fifth for the greatest number of preterm births. Preterm infants may inflict various complication as the result of underdeveloped immunity, affecting their growth and development in the long run until they reach adult phase. Such complications could be prevented through adequate nutrition fulfillment. Purpose: This article aimed to elaborate the characteristics of growth and development of premature babies, long term effect on the development and the impact of immunity and gut health of preterm infants in supporting their growth and development. Methods: References cited in this article were obtained from the latest primary literature within the last 10 years. Discussion: The rate and ability of infants to perform catch-up growth depends on the birth weight and gestation age, at which the lower birth weight and lower gestational age had slower rate. Brain structures that of preterm infants differ compared to the term, and these changes give rise to various clinical outcomes, including long term emotional, behavioral changes, cognitive and executive functioning. Immature immune system in preterm infants reduces the protective ability by innate and adaptive immunity in overcoming pathogens compared to term infants, including gut microbiota prematurity which affects nutrition absorption and growth and development catch up ability. Appropriate and adequate nutrition supplementation has shown beneficial effects in promoting the growth of normal gut flora, which allow better absorption of nutrition and therefore enhancing growth rate and supporting the development of preterm infants. Conclusions: Optimal growth and development of preterm infants are supported by sufficient nutrition supplementation to support the growth of gut microbiota, facilitating the catch-up growth and development of premature infants and immune system maturity.